Konsep Perencanaan Botanic Edu-Garden untuk Mendukung Perwujudan Agropolitan Pattallassang, Kabupaten Gowa, Sulawesi Selatan - Mega Indah Lestari; Muh Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
To support the Vision of Gowa Regency, it is necessary to develop botanical edu-garden in improving the quality of society by improving the quality of the environment and public awareness of sustainable environmentally friendly infrastructure. The research and conservation strategies of Botanic Edu-Garden are used to provide direct benefits to regional, national and international communities in supporting community thinking about the need for equality and social responsibility around issues of plant conservation and climate change. This study aims to explore the concept of ideal botanic edu-garden planning in the best cities in the world, identify the potential of Pattalassang District in the implementation of the edu-garden botanic planning concept and make the concept of botanic edu-garden planning in Pattalassang District. The analytical method used is descriptive comparative analysis, analysis of the proportion of population, spatial analysis and analysis of economic, social and environmental potential to formulate the concept of edu-garden botanic planning. The results of the analysis indicate the purpose of edu-park botany development affects the facilities to be built. Pattalassang District is very strategic as the location of the Botanic Edu-Garden development site. The concept of planning that was formulated was a botanical edu-park which was mostly adapted from the Brooklyn Botanic Gardens.